Fluorescence Sensor with A New ON1–OFF–ON2 Switching Mechanism Using the Excited State Intermolecular Proton Transfer Reaction of An Anthracene‐diurea Compound. (10th June 2017) - Matsumoto, Hisato; Nishimura, Yoshinobu; Arai, Tatsuo
Abstract: A new photoreaction mechanism of "Three‐state molecular switch" fluorescence sensor based on ON 1 ‐OFF‐ON 2 sequence was achieved by anthracene‐diurea compound, which was designed using two phenylurea groups and one anthracene, 9, 10BtDSPUA. Photochemical properties of 9, 10BtDSPUA and interaction between 9, 10BtDSPUA and anion were investigated in detail by absorption, 1 H NMR, fluorescence, and fluorescence decay measurements. While the fluorescence of 9, 10BtDSPUA in DMSO (ON 1 ) was quenched in the presence of low concentration of acetate anion (OFF), fluorescence enhancement occurred by the addition of high concentration of acetate anion (ON 2 ). This compound forms complex with acetate anion through hydrogen bonding interaction in the ground state resulted in tautomer formation by excited state intermolecular proton transfer (ESIPT) on irradiation. Whereas single coordination of acetate anion to anthracene‐diurea compound may cause fluorescence quenching, full coordination may cause fluorescence enhancement due to suppressing ESIPT. This suppressing ESIPT was occurred by electron‐donating resonance effect between two urea moieties. This study is the first example of ON 1 ‐OFF‐ON 2 fluorescence sensor for concentration detection of acetate anion. Abstract : A new photoreaction mechanism of "Three‐state molecular switch" fluorescence sensor based on ON 1 ‐OFF‐ON 2 sequence was achieved by anthracene‐diurea compound, which was designed using two phenylurea groups and one anthracene, 9, 10BtDSPUA. While the fluorescence of 9, 10BtDSPUA in DMSO (ON 1 ) was quenched in the presence of low concentration of acetate anion (OFF), fluorescence enhancement occurred by the addition of high concentration of acetate anion (ON 2 ). Whereas single coordination of acetate anion to anthracene‐diurea compound may cause fluorescence quenching, full coordination may cause fluorescence enhancement due to suppressing ESIPT.